Wzory do Obliczeń Przepływu Gazu w Nachylonych Gazociągach - Walden, H. (Engineering Transactions, 1961)
The general case of flow is considered, the coefficient of linear resistance being accounted for in the range of turbulent flow. The equations obtained may be applied not only to the computation of inclined and horizontal pipes but also to vertical gas. In the general equation of flow the author’s empirical formulae are taken into account for the coefficient of hydraulic resistance, in function of the Reynold’s number and the roughness of the pipe.